Patients’ Perspectives on Social Barriers to Care and the Acceptability and Impact of a Community Health Worker Program in Outpatient Ophthalmology - Rustam Z; Amezcua Moreno J; Tran D; Ferguson K; Woods R; Cai CX (Clinical Ophthalmology)
Zainab Rustam,1 Jose Amezcua Moreno,1 Diep Tran,1 Kenya Ferguson,2 Randi Woods,2 Cindy X Cai1,3 1Wilmer Eye Institute, Johns Hopkins School of Medicine, Baltimore, MD, USA; 2Sisters Together and Reaching, Inc, Baltimore, MD, USA; 3Department of Biomedical Informatics and Data Science, Johns Hopkins School of Medicine, Johns Hopkins University, Baltimore, MD, USACorrespondence: Cindy X Cai, Wilmer Eye Institute, 1800 Orleans Street, Room 711, Baltimore, MD, 21287, USA, Tel +1 410 502-2789, Email ccai6@jhmi.eduIntroduction: Community Health Workers (CHWs) are trusted members of the community who can work as an integral liaison between community members and health care to address adverse social determinants of health (SDoH). The purpose of this semi-qualitative study was 1) solicit patient-reported social needs and what they consider barriers to their ophthalmic care, 2) determine the acceptability of discussing SDoH in eye care, and 3) determine the acceptability of leveraging a CHW to address social needs.Methods: A total of 50 adults with type 2 diabetes at the Wilmer Eye Institute participated in semi-structured interviews. The interview included questions on barriers to care, acceptance of SDoH discussion in eye clinics, ideas to address SDoH and acceptability of CHWs. The transcripts were analyzed using traditional text analysis based on classic grounded theory to identify themes.Results: Patients reported transportation (66%), scheduling conflicts (50%), forgetting appointments (50%) and other illnesses (40%) as barriers to attending eye appointments. Motivators included knowing the importance of maintaining regular eye appointments (22%), desire to maintain eyesight (22%) and health (10%). 88% felt positive about addressing SDoH in the eye clinic but were apprehensive about the front desk (14%) asking the questions citing lack of privacy. Some preferred doctors (20%) or specialized staff (14%) to ask the questions. 82% felt no topics should be off limits, understanding that questions aimed to help them. Ideas to address SDoH in eyecare included improving communication (44%), increasing resource access (36%) and introducing social workers (32%). 16% were aware of existing social services for eyecare. After explaining the role of CHWs, (90%) were enthusiastic about incorporating CHW in eyecare.Conclusion: These findings support the assessment of SDoH in ophthalmology clinics and the integration of CHWs to address social needs from the patients’ perspectives.Keywords: diabetic retinopathy, social determinants of health, barriers to care, social needs